Pengaruh Mekanisme Good Corporate Governance Terhadap Nilai Perusahaan Sektor Energi Yang Terdaftar Di Bursa Efek Indonesia - Ni Putu Dinda Dewi; Ni Wayan Alit Erlinawati; Ni Made Wisni Arie Pramuki (UNHI Press, 2025)
Company value is an indicator of investor assessment. Company value is often related to investors' views on the level of success of a company which is influenced by share prices, so that if the share price is high then the company value can be high. This research examines the influence of good corporate governance mechanisms on the value of energy sector companies listed on the Indonesian stock exchange. The GCG mechanism in this research is proxied by independent commissioners, institutional ownership, managerial ownership, board of directors and audit committee. The population in this research is all energy sector issuers registered on the IDX in 2022. The sample in this research is 72 energy sector issuers. The analysis technique used is multiple linear regression. The research results show that independent commissioners, institutional ownership and managerial ownership have a negative but not significant effect on firm value. Another finding in this research is that the board of directors is able to increase company value and the audit committee has a positive but not significant influence on company value.